Improved reference genome of Aedes aegypti informs arbovirus vector control. (22nd November 2018) - Matthews, Benjamin; Dudchenko, Olga; Kingan, Sarah; Koren, Sergey; Antoshechkin, Igor; Crawford, Jacob; Glassford, William; Herre, Margaret; Redmond, Seth; Rose, Noah; Weedall, Gareth; Wu, Yang; et al.
Abstract FemaleAedes aegypti mosquitoes infect more than 400 million people each year with dangerous viral pathogens including dengue, yellow fever, Zika and chikungunya. Progress in understanding the biology of mosquitoes and developing the tools to fight them has been slowed by the lack of a high-quality genome assembly. Here we combine diverse technologies to produce the markedly improved, fully re-annotated AaegL5 genome assembly, and demonstrate how it accelerates mosquito science. We anchored physical and cytogenetic maps, doubled the number of known chemosensory ionotropic receptors that guide mosquitoes to human hosts and egg-laying sites, provided further insight into the size and composition of the sex-determining M locus, and revealed copy-number variation among glutathioneS -transferase genes that are important for insecticide resistance. Using high-resolution quantitative trait locus and population genomic analyses, we mapped new candidates for dengue vector competence and insecticide resistance. AaegL5 will catalyse new biological insights and intervention strategies to fight this deadly disease vector. An improved, fully re-annotatedAedes aegypti genome assembly (AaegL5) provides insights into the sex-determining M locus, chemosensory systems that help mosquitoes to hunt humans and loci involved in insecticide resistance and will help to generate intervention strategies to fight this deadly disease vector.